2017
DOI: 10.1021/acs.jpcc.6b09274
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure of Core–Shell MnFe2O4+δ-Based Nanocrystals: Cation Distribution and Valence States of Manganese Ions

Abstract: We investigate the local structure of nanoparticles based on a manganese ferrite core surrounded or not by a maghemite layer obtained after hydrothermal surface treatment. Results of X-ray powder diffraction (XRD) and neutron powder diffraction (NPD) measurements are crossed with those of infield Mossbauer spectroscopy and X-ray absorption spectroscopy (XANES/EXAFS) to study the valence state of Mn ions and the cation distribution at interstitial sites of the core−shell nanoparticle structure. Linear combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 56 publications
6
33
1
2
Order By: Relevance
“…The calculation of the molar fraction is given by, χ m = [Mn]/([Mn] + [Fe]). Studies correlated to this mechanism of the core-shell model were reported in the works of Gomes et al [34], Martins et al [23], and Pilates et al [26]. Figure 1a presents the TEM picture of the sample and shows that the NPs are roughly spherical.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…The calculation of the molar fraction is given by, χ m = [Mn]/([Mn] + [Fe]). Studies correlated to this mechanism of the core-shell model were reported in the works of Gomes et al [34], Martins et al [23], and Pilates et al [26]. Figure 1a presents the TEM picture of the sample and shows that the NPs are roughly spherical.…”
Section: Resultsmentioning
confidence: 65%
“…An excess of positive charges occurs due to the oxidation of Mn +2 to Mn +3 in the synthesis process, in order to balance exactly the extra positive charge that appears in the formula is inserted a δ parameter of 0.48 to adjust the electronegativity. In recent works by Martins et al [23] and Moreira et al [33], the mean valence of manganese in ferrites synthesized by coprecipitation was determined. Several analyzes were performed, including the X-ray Absorption Near Edge Structure (XANES) analysis with the Linear Combination Fitting (LFC) method of Mn 3 O 4 , Mn 2 O 3 and MnO 2 oxides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mössbauer spectrum is shown in Figure c, where Co 2 FeO 4 /NCNTs exhibits superparamagnetic behavior. The composite system could be fitted with two symmetric quadrupole doublets with Lorentzian line shapes and isomer shifts and quadrupole splitting of δ(A1)=0.37 mm s −1 , Δ E Q (A1)=0.60 mm s −1 , and δ(A2)=0.46 mm s −1 , Δ E Q (A2)=0.92 mm s −1 at 300 K. The parameters clearly indicate that the two subspectra correspond to iron at M Oct and M Td sites of the Co 2 FeO 4 /NCNTs . The ratio of Fe 3+ Oct to Fe 3+ Td is 2.57 by integration of the A2/A1 components, indicating that oxide is a hybrid spinel (Co 0.72 Fe 0.28 ) Td (Co 1.28 Fe 0.72 ) Oct O 4 .…”
Section: Figurementioning
confidence: 94%
“…[17] TheM çssbauer spectrum is shown in Figure 1c,w here Co 2 FeO 4 /NCNTs exhibits superparamagnetic behavior.T he composite system could be fitted with two symmetric quadrupole doublets with Lorentzian line shapes and isomer shifts and quadrupole splitting of d(A1) = 0.37 mm s À1 , DE Q (A1) = 0.60 mm s À1 ,and d(A2) = 0.46 mm s À1 , DE Q (A2) = 0.92 mm s À1 at 300 K. The parameters clearly indicate that the two subspectra correspond to iron at M Oct and M Td sites of the Co 2 FeO 4 /NCNTs. [18] Theratio of Fe 3+ Oct to Fe 3+ Td is 2.57 by integration of the A2/ A1 components,i ndicating that oxide is ah ybrid spinel (Co 0.72 Fe 0.28 ) Td (Co 1.28 Fe 0.72 ) Oct O 4 .T he isomer shift (d), ad escriptor of the valence state of the Mçssbauer absorber atom, indicates that Fe exists mainly in trivalent form with high crystal field stabilization energy,a nd thus can partly replace Co atoms situated on the octahedral 16 b sites of the Co 3…”
Section: Redox-inert Fe 3+ Ions In Octahedral Sites Of Co-fespinel Oxmentioning
confidence: 99%